Low-Dose Treatment with Erythropoiesis-Stimulating Agents and Cardiovascular Geometry in Chronic Kidney Disease: Is Darbepoetin-α More Effective than Expected? - Di Lullo, Luca (S. Karger AG, 2012)
INTRODUCTION: Chronic kidney disease (CKD) is a widespread invalidating condition, leading to erythropoietin deficiency and decreased cardiovascular performance. Darbepoetin-α and epoetin-α are extensively used to correct renal anemia. The aim of this study was to evaluate cardiological outcomes in two groups of CKD patients treated with erythropoiesis-stimulating agents (ESA: 20 μg darbepoetin-α weekly vs. 2,000 IU epoetin-α thrice weekly) with an unconventional 1:300 conversion ratio. METHODS: The study was designed as a single center, retrospective, observational study. One hundred stage IV CKD patients were selected. Hemoglobin (Hb), hematocrit, C-reactive protein, pro-brain natriuretic peptide (BNP) and basal echocardiograms were monitored every 3 months. RESULTS: Darbepoetin-α was significantly more effective in increasing Hb levels after 3 (p < 0.0001), 6 (p < 0.0001), 9 (p < 0.01) and 12 months (p < 0.01) compared to epoetin-α. The optimal Hb target level (11 g/dl < Hb < 12 g/dl) was completely reached after 1 year of treatment with darbepoetin-α and in 70% of the patients treated with epoetin-α (p < 0.01). Cardiovascular performance (left ventricular end-diastolic volume, ejection fraction and pro-BNP) was significantly improved after darbepoetin-α treatment at the 6- and 12-month follow-ups compared to epoetin-α. Discussion: Despite the limitations of a retrospective observational study, these results encourage nephrologists to test the 1:300 darbepoetin/epoetin conversion ratio in ‘easy’ patients, and aggressive protocols for the treatment of anemia in CKD patients are avoided. Darbepoetin-α appeared effective in anemia correction, improving cardiovascular performance in a significantly higher proportion than epoetin. At low doses, on the other hand, it has to be borne in mind that a treatment regimen with only one submaximal administration per week may increase patient compliance and adherence to therapy, explaining in part the observed results.